2022
DOI: 10.3390/biology11050786
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping the Mountains of Giants: Anthropometric Data from the Western Balkans Reveal a Nucleus of Extraordinary Physical Stature in Europe

Abstract: The inhabitants of the Dinaric Alps (former Yugoslavia and Albania) have long been known as people of impressive body height, but after World War II, there was a critical lack of data related to this phenomenon. This anthropological synthesis includes the measurements of 47,158 individuals (24,642 males and 22,516 females) from the period 2010–2018 and maps detail regional differences in male stature in the Western Balkans. According to these data, young men from Montenegro (182.9 cm) are currently the tallest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Virtually all I2a-P37.2 in the Dinaric Alps is represented by its subbranch I2a-M423 (I2a1a2) [48][49] The work of our research team [50] identified a geographical nucleus with extraordinarily tall statures (≥184 cm), which includes Dalmatia, Herzegovina, and the northwestern parts of Montenegro (Figure 13), and agrees with the regional distribution of Y hg I [45,47,49]. However, the Western Balkan area is characterized by several peculiarities: First, the ratio between Y hg I and Villabruna k=7 or BHG k=12 ancestry in the Western Balkans is higher than in Scandinavia, indicating a stronger male founder effect over a genetically alien substrate.…”
Section: The Complex Origin Of the Dinaric Phenomenonmentioning
confidence: 99%
“…Virtually all I2a-P37.2 in the Dinaric Alps is represented by its subbranch I2a-M423 (I2a1a2) [48][49] The work of our research team [50] identified a geographical nucleus with extraordinarily tall statures (≥184 cm), which includes Dalmatia, Herzegovina, and the northwestern parts of Montenegro (Figure 13), and agrees with the regional distribution of Y hg I [45,47,49]. However, the Western Balkan area is characterized by several peculiarities: First, the ratio between Y hg I and Villabruna k=7 or BHG k=12 ancestry in the Western Balkans is higher than in Scandinavia, indicating a stronger male founder effect over a genetically alien substrate.…”
Section: The Complex Origin Of the Dinaric Phenomenonmentioning
confidence: 99%
“…Mesin perontok padi yang ada belum didesain dengan mempertimbangkan aspek ergonomi dan belum sesuai postur tubuh petani. Postur tubuh manusia di dunia beragam ada orang Asia dengan perawakan kecil, Eropa dan Afrika dengan perawakan besar, Melayu, dan Jawa dengan perawakan lebih kecil dari Asia Timur Raya (Grasgruber and Masanovic, et al 2022;Grasgruber and Mašanović, et al 2022;Suryadarma, 2019).…”
Section: Pendahuluanunclassified
“…In the original publication [ 1 ], the authors’ surnames were listed without diacritics. At the same time, Natasa M. Mihailovic should not have a middle name.…”
Section: Authors’ Namesmentioning
confidence: 99%